A Clinical Case Control Study to Evaluate the Prognosis of Dental Implant Treatment in Japanese Patients with Periodontal Disease - YAJIMA, Yasutomo; NORIZUKI, Yoshie; ITO, Taichi; MORI, Gentarou; OGASAWARA, Ryuichi; KIDA, Kouichi; ODA, Yukari; FURUYA, Yoshitaka (Journal of Japanese Society of Oral Implantology, 2020)
Patients with periodontal disease are also reported to be susceptible to infection of peri-implant tissue. The purpose of this study was to evaluate clinically the effects of periodontal disease on the prognosis of implant treatment in Japanese patients.The subjects of the survey were 34 Japanese patients who received implants at Tokyo Dental College Hospital, Department of Oral Implantology. Based on the examination of periodontal disease at the first visit, the patients were divided into two groups, 14 healthy patients (N P group) and 20 periodontal disease patients (P group). Remaining number of teeth, bleeding on probing (BOP) and probing pocket depth (PPD) in natural teeth, age-related periodontal bone loss (ArB) score, and resorption degree of bone around implant (at the time of installation of superstructure, and at 3 years after installation) was evaluated. In all cases, appropriate periodontal disease treatment was performed and then implant treatment was performed.After more than 3 years after installation of the implant superstructure, no significant difference was observed between both groups in BOP, rate of PPD of teeth of 4 mm or more, or even rate of PPD of teeth of 6 mm or more. Not significant difference was observed in the ArB score. No implants fell out during the test period, and the extent of absorption of alveolar bone of the implant unit was slight. However, a significant difference was observed in the extent of absorption of alveolar bone of the implant unit between the two groups.From the results of clinical parameters of periodontal disease, it is suggested that the risk of worsening of periodontal disease is reduced by performing implant preoperative periodontal disease treatment and maintenance after implant treatment.